Software Tool for the Extrinsic Calibration of Infrared and RGBD Cameras Applied to Thermographic Inspection - Aza Taimal, Jaimen Junior; Bacca Cortes, Bladimir; Restrepo Girón, Andrés David (Ingeniería, 2022)
Context: Thermographic inspections are currently used to assess energy efficiency in electrical equipment and civil structures or to detect failures in cooling systems and electrical or electronic devices. However, thermal images lack texture details, which does not allow for a precise identification of the geometry of the scene or the objects in it. Method: In this work, the development of the software tool called DepTherm is described. This tool allows performing intrinsic and extrinsic calibration between infrared and RGBD cameras in order to fuse thermal, RGB, and RGBD images, as well as to record thermal and depth data. Additional features include user management, a visualization GUI for all three types of images, database storage, and report generation. Results: In addition to the integration tests performed to validate the functionality of DepTherm, two quantitative tests were conducted in order to evaluate its accuracy. A maximum re-projection error of 1,47±0,64 pixels was found, and the maximum mean error in registering an 11 cm side cube was 4,15 mm. Conclusions: The features of the DepTherm software tool are focused on facilitating thermographic inspections by capturing 3D scene models with thermal data.